Mutu teh celup dengan campuran bubuk sereh (Cymbopogon citratus) dan bubuk kelor (Moringa oleifera) - Rahman, Suburi; Dwiani, Afe (UNIVERSITAS MUHAMMADIYAH MATARAM, 2022)
Moringa is one of potential raw material of herbal tea. Moringa tea had disadvantage is a off-flavour aroma. The addition of lemongrass hopefully can reduce the off-flavour aroma and improve the quality of tea. This research aimed to determine the effect of mixing lemongrass powder and moringa powder on the quality of teabags. The method that used in this study was complete randomized design (CRD) that was treatment P1 = 100% moringa leaf powder: 0% lemongrass powder; P2 = 80% moringa leaf powder: 20% lemongrass powder; P3 = 60% moringa leaf powder: 40% lemongrass powder; P4 = 40% moringa leaf powder : 60% lemongrass powder and P5 = 20% moringa leaf powder : 80% lemongrass powder. The data were analyzed using analysis of variance at a level of 5% and if there were real differences, tests continued using the LSD (least significant difference) at the same level. Based on the results of the analysis, it is known that the treatment has a significant effect on chemical quality (antioxidant activity, moisture content, and pH) and organoleptics (color and aroma), while it has no significant effect on the organoleptic taste in teabags. The best treatment for the chemical quality of teabags is produced by P2 treatment (80% moringa powder: 20% lemongrass powder) with antioxidant activity of 88.64%; moisture content of 6.44% and pH of 6.0. The best treatment for the organoleptic quality of hedonic tea bag color is produced by P2 treatment (80% Moringa powder: 20% lemongrass powder) with a value of 3.55 (like criteria) and for hedonic teabag aroma produced by P5 treatment (20% moringa leaf powder: 80 % lemongrass powder) with a value of 3.45 (rather like criteria).